2017
DOI: 10.1002/smi.2766
|View full text |Cite
|
Sign up to set email alerts
|

Associations between psychological stress and smoking, drinking, obesity, and high blood pressure in an upper middle‐income country in the African region

Abstract: The direction and magnitude of the associations between cardiovascular risk factors (CVRFs) and psychological stress continue to be debated, and no data are available from surveys in the African region. In this study, we examine the associations between CVRFs and psychological stress in the Seychelles, a rapidly developing small island state in the African region. A survey was conducted in 1,240 adults aged 25-64 years representative of the Seychelles. Participants were asked to rank psychological stress that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…This may be due to an interaction of perceived stress and smoking or alcohol status [71]. Previous studies have indicated that smokers may be smoking to relieve perceived stress [72], but this relief is temporary; smoking was found to lead to higher perceived stress overall [72]. Similarly, some individuals exhibiting problematic internet use may spend more time on the internet to escape perceived stress, but end up experiencing higher perceived stress.…”
Section: Negative Feelings Perceived Stress Smoking Status and Alcohol Assumption Statusmentioning
confidence: 99%
“…This may be due to an interaction of perceived stress and smoking or alcohol status [71]. Previous studies have indicated that smokers may be smoking to relieve perceived stress [72], but this relief is temporary; smoking was found to lead to higher perceived stress overall [72]. Similarly, some individuals exhibiting problematic internet use may spend more time on the internet to escape perceived stress, but end up experiencing higher perceived stress.…”
Section: Negative Feelings Perceived Stress Smoking Status and Alcohol Assumption Statusmentioning
confidence: 99%
“…Additional behavioral targets, including stress reduction, have been proposed [10]. Stress is a pathological process resulting from psychophysiological responses triggered by threats to homeostasis [11], and chronic psychosocial stress leads to an increase in BP and the risk of developing hypertension [12][13][14]. Moreover, it is now established that chronic conditions frequently present with various types of psychopathology such as depressive aspects, cognitive-behavioral disorders, sleep disorders, and extremely high levels of stress [15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In conjunction with Harrell's (2000) model, other models such as the tension-reduction model (Conger, 1956) and affect regulation model (Cooper, Frone, Russel, & Mudar, 1995) similarly contend that AAs may consume alcohol in problematic ways to cope (e.g., avoidance coping) with racism-related stress. Heavy, stressrelated drinking can consequently generate vulnerabilities for alcohol-related illnesses such as cardiovascular disease (Chamik, Viswanathan, Gedeon, & Bovet, 2018). Thus, it is tenable to earmark RD as a contributor to racial health inequities that can accelerate health deterioration by increasing the risk for physical consequences tied to heavy alcohol consumption for AA emerging adults.…”
Section: Racial Discrimination and Physical Consequences Of Alcohol Consumptionmentioning
confidence: 99%